Bifosfonatos (BFs) como transportadores osteotrópicos no planejamento de fármacos dirigidos - Castro, Lúcia Fioravanti [UNESP]; Silva, Antonio Távora de Albuquerque [UNESP]; Chung, Man-Chin [UNESP]; Ferreira, Antonio Gilberto; Ferreira, Elizabeth Igne (Sociedade Brasileira de Química, 2004)
Drug therapy involving bone tissue diseases is difficult, calling for the design of specific drugs. The present paper is a brief review of a new site-directed system termed ODDS (osteotropic drug delivery system), based on a latenciation process, using bisphosphonates as bone carriers. This is an important tool for the rational prodrug design for obtaining selective drugs.
Bisphosphonates as osteotropic carriers for designing site-directed drugs
Keywords: bisphosphonates; prodrugs; ODDS